Variants and Pitfalls in MR Imaging of Knee Injuries - Tan, Hsien Khai; Bakri, Mohammad M.; Peh, Wilfred C.G. (Seminars in Musculoskeletal Radiology, 2014)
MR imaging is an established tool for the detection and diagnosis of various injuries and internal derangements of the knee, enabling excellent anatomical visualization and producing good soft tissue contrast and characterization. However, numerous normal variants and potential pitfalls may lead to diagnostic errors. Understanding the basic MR imaging principles, applying the correct technique, knowing the normal anatomy and variants, recognizing artifacts, and assuring good clinical and radiographic correlation helps avoid these potential pitfalls.
Keywords: diagnostic errors; knee normal variants; knee pseudolesions; MR imaging pitfalls